FAKTOR MEMPENGARUHI PERKEMBANGAN AFEKTIF : FAKTOR MEMPENGARUHI PERKEMBANGAN AFEKTIF - Urik Taurik; Imam Mashudi (LPPM UNiversitas Bina Mandiri Gorontalo, 2022)
ABSTRACT Talking about affective, of coirse, we are pleased with fear or love, affect circumastance, feelings and emotions, have a style or meaning that shows feeling, actions or behavior that are accompanied by certain feelings called affective colors, so adolescent development is greatly influenced by individual emotional development. In general, a person's life is full of encouragement and interest toachieve or have something. How many drives and interest the has is the basis of his emotional experience. The journey of one's life is not the same. Different desires and interest are owned by each individual according to their respective lifestyle. Ini additional, the way or method used to realize the interest and desires that are driven by e-motion are different from one another.